Early Experience with the ACA: Coverage Gains, Pooling of Risk, and Medicaid Expansion. Issue 4 (December 2016) - Blumberg, Linda J.; Holahan, John
We provide an overview of the characteristics of those who have gained insurance coverage due to the ACA as well as the characteristics of the remaining uninsured. We also describe the implications for the broader sharing of health care risks required under the law, and how they vary by individuals' health status. Finally, we assess the implications of state decisions to expand or not expand Medicaid eligibility under the law, how those decisions affect state finances, health care providers, residents, and how the effects may vary for those states using waivers to expand eligibility using strategies designed to be more broadly politically acceptable.